Simultaneous : a novel - Heisserer, Eric (Flatiron Books, 2025)
Federal agent Grant Lukather works for an unknown department of Homeland Security called Predictive Analytics. They look for patterns in tips and chatter to prevent a terrorist event before it happens. One of these calls, about a possible explosion in New Mexico, leads Grant to a case with unimaginable consequences. He meets Sarah Newcomb, a therapist who uses past-life hypnosis in her treatment but has recently stumbled upon a phenomenon that seems to defy logic. Grant follows this thread to another crime: a copycat killer case in Colorado. With the help of one of Sarah's patients, they embark upon an investigation that spans multiple states, timelines, and consciousnesses. With limited time and only a tenuous grasp of how this phenomenon works, the unlikely trio are in a race for their lives--past, present, and future.